Impact of Cardiopulmonary Resuscitation on Cardiac Transplantation outcome - Mojtabaee, Meysam; Naghashzadeh, Farah; Ghorbani, Fariba; Ghafarian, Shahrzad; Shahryari, Shagin; Sadegh Beigee, Farahnaz (International Journal of Cardiovascular Practice, 2019)
Introduction: Donor heart shortage limits heart transplantations programs while the number of patients waiting for cardiac transplant continues to increase. Optimizing the use of all available donor hearts is a vital key to reduce waiting list mortality. Among different extended criteria, prolong cardiopulmonary resuscitation (CPR), i.e. more than 20 min, has been considered under doubt to be a selection criterion in donor selection. The aim of this study was to compare the outcomes of heart transplantation from cardiopulmonary-resuscitated donors to those who received hearts from donors who did not require cardiopulmonary resuscitation.Methods: This study was a retrospective analysis of adult heart transplantation program in Masih Daneshvari Hospital in Tehran, Iran from 2010 to 2019. Donors and recipients? demographics, cause of end-stage heart disease and brain death, duration of hospitalization for both donors and recipients and also the duration of cardiopulmonary resuscitation and other factors related to it were investigated. Qualitative variables were compared using Chi-square test. Quantitative variables were compared using T-test. Patient and graft survival rates were calculated using the actuarial method and compared using Wilcoxon's test.Results: Among 92 recipients, 39 were transplanted with cardiac grafts from CPR-suffering donors. There were no significant differences regarding sex, age, donor and recipient hospitalization periods, early rejection and 1-year-survival rate considering CPR and non-CPR grafts. However, we detected a strong negative correlation between the duration of CPR and 3-year-survival rate (P = 0.02 and R-value = -0.62) and also its association with post-transplant arrhythmias (P = 0.04).Conclusion: There is a negative possible influence of long-lasting CPRs (especially more than 20 minutes) in midterm survival and post-transplant complications.